2012
DOI: 10.1186/1756-3305-5-176
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and evaluation of a Sarcoptes scabiei allergen as a candidate vaccine

Abstract: BackgroundSarcoptic mange caused by the mite Sarcoptes scabiei is a worldwide disease affecting both humans and animals. Here we report the molecular characterization and evaluation of a recombinant S. scabiei tropomyosin (SsTm) protein in a vaccination trial in rabbits.MethodsThe full-length cDNA was cloned in a bacterial pET vector, and the recombinant protein was expressed in BL21 (DE3) cells and purified. Using specific rabbit antiserum, tropomyosin was localized immunohistochemically in mite tissue sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 38 publications
1
26
0
2
Order By: Relevance
“…Recombinant Sarcoptic scabiei tropomyosin (SsTm) is an immunogenic protein that has been evaluated in sarcoptic mange of rabbits. It failed to show efficacy and probably requires alternative adjuvants or delivery methods to be developed into an effective vaccine . A Sarcoptes scabiei var cuniculi DNA vaccine, which encodes paramyosin, was immunogenic and elicited both humoral and cellular immunity in mice .…”
Section: Immunotherapy and Vaccinesmentioning
confidence: 99%
“…Recombinant Sarcoptic scabiei tropomyosin (SsTm) is an immunogenic protein that has been evaluated in sarcoptic mange of rabbits. It failed to show efficacy and probably requires alternative adjuvants or delivery methods to be developed into an effective vaccine . A Sarcoptes scabiei var cuniculi DNA vaccine, which encodes paramyosin, was immunogenic and elicited both humoral and cellular immunity in mice .…”
Section: Immunotherapy and Vaccinesmentioning
confidence: 99%
“…Therefore, several studies have been aimed at developing molecular subunit vaccines using recombinant DNA cloned from S. scabiei. [16][17][18][19] 8000 12 Next, PCR to amplify a 289 bp region of the COX1 gene was performed using the forward primer 5'-TCTTAGGGGCTGGATTTAGTATG-3' and the reverse primer 5'-AGTTCCTCTACCAGTTCCAC-3'. PCR was performed in an automatic thermocycler (Biorad) with an initial denaturation step at 95 °C for 5 min, and 35 cycles of 94 °C for 1 min, 55 °C for 1 min, and 72 °C for 1 min, followed by a final extension step at 72 °C for 5 min.…”
Section: Scabies Disebabkan Oleh Tungau Sarcoptes Scabiei Adalah Tungmentioning
confidence: 99%
“…Second, we have not seen any published references indicated that QuilA adjuvant might depress IgE levels. At last, a colleague in our laboratory had finished her study with exact the same doze of the same adjuvant (QuilA), and the results of her study did not show IgE depression in S. Scabiei ‐infected rabbits . Therefore, we concluded that it was not the QuilA adjuvant that depressed IgE levels, but something else which worth more further study in the future.…”
Section: Discussionmentioning
confidence: 90%